Sex Differences in Time to Treat and Outcomes for Gliomas - Stabellini, Nickolas; Krebs, Halle; Patil, Nirav; Waite, Kristin; Barnholtz-Sloan, Jill S. (Frontiers in Oncology, 2021)
Background. Gliomas are the most common type of primary malignant brain tumor in adults, representing one third of all primary and central nervous system (CNS) tumors and 80% of malignant tumors diagnosed in the Western world. Epidemiological data indicate that the overall incidence and mortality of cancer is higher in males, while females have a better prognosis. The goal of this study is to determine whether there are sex differences in the time to treat and clinical outcomes in patients with gliomas. Methods. Glioblastoma (GB) and Lower Grade Glioma (LGG) patients were defined per the Central Brain Tumor Registry of the United States (CBTRUS) from the National Cancer Database (NCDB) for diagnosis years 2004 to 2016. Associations between sex and time to treatment variables as well as associations between sex and multiple clinical outcomes were assessed using univariable and multivariable models. Results. A total of 176,100 patients were used for analysis (124,502 GBM and 51,598 LGG). Males had a statistically significant association with >7 days to surgery (OR = 1.09, CI 1.05-1.13, p<0.001) but this association was not observed in the multivariable model (OR = 1.05, CI 0.96-1.16, p=0.25). After adjustment for key variables including time to treat variables, males with GBM and LGG had a higher risk of death (HR = 1.11, CI 1.09-1.13, p<0.001, HR = 1.09, CI 1.03-1.15, p <0.001; respectfully). Sex differences in 90-day mortality for GBM were not found after adjustment (OR for males = 0.99, CI 0.91-1.08, p=0.93). For LGG, both the univariable and multivariable logistic regression models showed no sex differences in 90-day mortality (OR for males = 1.03, CI 0.94-1.12, p=0.45; multivariable OR for males = 0.81, CI 0.62-1.06, p=0.13).